Book review Contested issues in training ministers in South Africa - K. T. Resane (Acta Theologica)
From text: This volume comprises eleven chapters, divided into three main sections, namely Structural realities of theological education; Ministerial formation challenges, and New developments. This is a sequel to another excellent edition entitled Between the real and ideal: Ministerial formation in South Africa (2012). The contributing authors are outstanding scholars and ministers in the field of Theology.